2022
DOI: 10.7759/cureus.26616
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Bacterial Etiology of Fournier’s Gangrene in an Immunocompetent Patient

Abstract: Fournier's gangrene (FG) is necrotizing fasciitis that affects the penis, scrotum, or perineum. Males are more likely to get affected by this disease. The most common predisposing risk factors are diabetes, alcoholism, hypertension, smoking, and immunosuppressive disorders. FG is a polymicrobial infection caused by both aerobic and anaerobic bacteria. The most common aerobic organisms are Escherichia coli, Klebsiella, Proteus, Staphylococcus, and Streptococcus. The most common anaerobic organisms are Bacteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…One limitation in our case report is the presence of a microbial infection that lacks a discernible etiology. The most prevalent risk factors for these infections include advanced age, urologic-related predisposing diseases, and immunosuppressive illnesses ( Lotte et al., 2016 ; Khan et al., 2022 ). However, none of these identified risk factors align with the characteristics exhibited by our patient.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation in our case report is the presence of a microbial infection that lacks a discernible etiology. The most prevalent risk factors for these infections include advanced age, urologic-related predisposing diseases, and immunosuppressive illnesses ( Lotte et al., 2016 ; Khan et al., 2022 ). However, none of these identified risk factors align with the characteristics exhibited by our patient.…”
Section: Discussionmentioning
confidence: 99%
“…It is not a common single-pathogen, often co-infecting with other microorganisms, and is considered an anaerobe coexisting in chronic wounds or diabetic ulcers [5]. Our literature review of reported cases infected by P. harei (Table 3) found instances involving implants, brain, abdomen, vessels, etc [4][5][6][7][8][15][16][17][18]. Only three cases of breast abscess caused by P. harei have been reported, all with concurrent actinomycosis infection[6-8] In contrast, our reported case of breast abscess caused by P. harei is unique, as it was a single infection without other identi ed pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…FG is usually a polymicrobial infection caused by aerobic Gram-negative bacilli or Gram-positive cocci. The most frequently identified bacterial species, upon culture, are Enterobacteriaceae, such as E. Coli , followed by streptococcal species [ 49 ]. Other organisms that are frequently isolated include Staphylococci , P. aeruginosa , Peptostreptococci , Bacteroides spp., and Clostridia [ 49 ].…”
Section: Discussionmentioning
confidence: 99%